Neo-Nationalism: Challenges for International Students - Lee, Jenny J (International Higher Education, 2016)
With increasing internationalization, national identity is being reintroduced and reconceptualized as forms of global competition. Neo-nationalism has the potential to negatively impact an international student’s experience, particularly in studying in one’s region. This article highlights some challenges for regional students in South Korea and South Africa based on neo-nationalism.